2009
DOI: 10.1007/s10681-009-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite markers in cultivated and wild species of sections Cepa and Phyllodolon in Allium

Abstract: The potential of microsatellite markers for use in genetic studies has 1 been evaluated in Allium cultivated species (Allium cepa, A. fistulosum) and its allied 2 species (A. altaicum, A. galanthum, A. oscaninii, A. roylei, A. vavilovii shallot and bulbonion but also for applying to segregation analyses in its F 2 population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Genomic SSRs require optimization of PCR conditions and amplify rarely in onion and allied Alliums McCallum et al 2008;Santos et al 2010). In contrast, Araki et al (2010) reported their amplification but it was in bulb onion and closely related species of section Cepa and Phyllodon only. EST-SSR primer set revealed an average of 3.2 amplicons (range, 1-7 alleles) and is equal to the average (3.6) reported by McCallum et al (2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic SSRs require optimization of PCR conditions and amplify rarely in onion and allied Alliums McCallum et al 2008;Santos et al 2010). In contrast, Araki et al (2010) reported their amplification but it was in bulb onion and closely related species of section Cepa and Phyllodon only. EST-SSR primer set revealed an average of 3.2 amplicons (range, 1-7 alleles) and is equal to the average (3.6) reported by McCallum et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Fischer and Bachmann (2000) were the first to develop and use genomic microsatellite primers in onion and allied species followed by development of expressed sequence tag (EST) derived microsatellites (Kuhl et al 2004;Martin et al 2005) and their utilisation for mapping (McCallum et al 2006) and cultivar discrimination McCallum et al 2008). Microsatellites have also been identified and characterised in Allium fistulosum L. (Song et al 2004;Tsukazaki et al 2007), garlic (Kim et al 2009) and tested for their applicability in onion and related wild species (Araki et al 2010). Despite so many reports, molecular marker application and diversity assessment in Indian bulb onions is still in its nascent stage.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2011) tested the transferability of 50 SSR markers of A. sativum in five Allium species, obtaining the highest transferability (73%) in A. ampeloprasum L. var porrum and the lowest (47.6%) in A. altaicum. Araki et al (2010) using 29 SSRs, derived from bulb onions, found a transferability rate ranging from 73.3% to 93.3% in six Allium species. Tsukazaki et al (2008) cross-amplified bulb onion EST-SSRs in bunching onions (A. fistulosum L.) with a value of 75.1% and Khar et al (2011) reported that the transferability of EST-SSR markers developed from A. cepa in the five Allium species achieved a ratio of 53.5%.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…The high level of transferability of SSR markers among three Rubus species means that they have a close genetic relationship with each other (Ipek et al 2009;Lee et al 2015). Similarly, high rates of transferability of SSR markers were reported in pine (94.2% between Pinus taeda and Pinus radiata), buckwheat (97.1% between Fagopyrum esculentum and Fagopyrum homotropicum), and onion (93.5% between Allium fistulosum and Allium altaicum) (Araki et al 2010;Chagné et al 2004;Ma et al 2009). …”
Section: Discussionmentioning
confidence: 96%